Wind of change: the impact of REPowerEU policy reforms on gas security - de Jong, Moniek (Policy Studies, 2024)
The Russian invasion of Ukraine was a shock to the EU gas market, as Russian gas supply dwindled and prices spiked. Previous exogenous shocks to the gas market resulted in policy reforms aimed at diversification and reducing dependency on Russian gas. However, their effectiveness was reduced. This study seeks to examine the policy changes under REPowerEU in light of gas security post-invasion. To examine this, three indicators–import dependency, diversification, and gas intensity–are used and examined the REPowerEU policy elements–reduced Russian gas, increased renewables and energy efficiency targets, gas storage requirements, demand reduction and a joint purchasing mechanism. This preliminary analysis highlights similarities in approaches, but also find that the severity of the crisis contributed to more support. The early effectiveness of the policy reforms is questioned, as change appear driven by other factors, such as decisions made by Russia and high gas prices.
Created from Fastlane, Scopus look-up
Keywords: diversification; Energy policy; energy security; European union; exogenous shocks; natural gas; Ukraine